The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1002/emp2.12104
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic changes in patients undergoing targeted temperature management

Abstract: Objectives Targeted temperature management is the recommended therapy for comatose patients after an out‐of‐hospital cardiac arrest resuscitation due to the reduction in neurological damage and improved outcomes. However, there may result in electrocardiographic instability depending on the degree of targeted temperature management, including minor or life‐threatening dysrhythmias or conduction delays. This project aims to describe the frequency of ECG interval changes and clinically relevant dysrhythmias in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Following serious health complications, such as a heart attack or stroke, which result in a drastically reduced blood supply to the brain, target temperature management is often employed to reduce the risk of neuronal damage [42]. However this treatment is also known to impact cardiac electrophysiology and can lead to the lengthening of the QT interval and the potential for lethal arrhythmias [14,42]. Similarly, using the exposed heart configuration, we also observed that subjecting zebrafish to hypothermia resulted in a significant increase in the QT interval.…”
Section: Discussionmentioning
confidence: 99%
“…Following serious health complications, such as a heart attack or stroke, which result in a drastically reduced blood supply to the brain, target temperature management is often employed to reduce the risk of neuronal damage [42]. However this treatment is also known to impact cardiac electrophysiology and can lead to the lengthening of the QT interval and the potential for lethal arrhythmias [14,42]. Similarly, using the exposed heart configuration, we also observed that subjecting zebrafish to hypothermia resulted in a significant increase in the QT interval.…”
Section: Discussionmentioning
confidence: 99%
“…Following serious health complications, such as a heart attack or stroke, which result in a drastically reduced blood supply to the brain, target temperature management is often employed to reduce the risk of neuronal damage [39]. However this treatment is also known to impact cardiac electrophysiology and can lead to the lengthening of the QT interval and the potential for lethal arrhythmias [35,39]. Similarly, using the exposed heart configuration, we also observed that subjecting zebrafish to hypothermia resulted in a significant increase in the QT interval.…”
Section: Discussionmentioning
confidence: 99%
“…Such low temperatures are rarely used nowadays, but with methods like SCD without automated control for hypothermia induction when used, the chances of overshooting hypothermia are not uncommon. Sinus bradycardia is the most common conduction abnormality seen during the cooling phase with studies showing prolongation of PR-interval, QTc prolongation, and ventricular escape rhythms [ 33 ]. No special attention is usually needed as they resolve during the rewarming phase.…”
Section: Reviewmentioning
confidence: 99%